2010
DOI: 10.1038/gene.2010.58
|View full text |Cite
|
Sign up to set email alerts
|

HLA (A-B-C and -DRB1) alleles and brain MRI changes in multiple sclerosis: a longitudinal study

Abstract: Several major histocompatibility complex (MHC) alleles have been postulated to influence the susceptibility to multiple sclerosis (MS), as well as its clinical/radiological course. In this longitudinal observation, we further explored the impact of human leukocyte antigen (HLA) class I/II alleles on MS outcomes, and we tested the hypothesis that HLA DRB1*1501 might uncover different strata of MS subjects harboring distinct MHC allele associations with magnetic resonance imaging (MRI) measures. Five hundred eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…In a recent study HLA‐B*44 positive patients, especially if HLA‐DRB1*1501 negative, are characterized by lower brain atrophy and T2‐lesion volume. In the presence of HLA‐DRB1*1501, however, HLA‐DRB1*10 was protective, but HLA‐DRB1*04 and HLA‐DRB1*14 were associated with higher T2‐lesion volume [19]. In contrast, an Australian study did not detect any influence of HLA‐DRB1 on disease severity, brain atrophy or cognition [20].…”
Section: Hla Genesmentioning
confidence: 94%
“…In a recent study HLA‐B*44 positive patients, especially if HLA‐DRB1*1501 negative, are characterized by lower brain atrophy and T2‐lesion volume. In the presence of HLA‐DRB1*1501, however, HLA‐DRB1*10 was protective, but HLA‐DRB1*04 and HLA‐DRB1*14 were associated with higher T2‐lesion volume [19]. In contrast, an Australian study did not detect any influence of HLA‐DRB1 on disease severity, brain atrophy or cognition [20].…”
Section: Hla Genesmentioning
confidence: 94%
“…Other HLA-variants have been linked with the risk of developing MS and subsequent disease severity, and these may interact with HLA-DRB*1501: For example, Liguori et al found in a longitudinal study of 518 people with MS, that in HLA-DRB1*1501 positive people, HLA-DRB1*10 was associated with a lower rate of WM lesion accrual (Liguori et al, 2011). Because of the limited number of subjects in our cohort we have focused on HLA-DRB1*1501 but future studies are warranted to explore the impact of other polymorphisms on MRI measures in MS.…”
Section: Discussionmentioning
confidence: 99%
“…The only other HLA-DR molecule that has been reported to be positively associated with MS severity is DRB1*04, but only when DRB1*15:01 (Liguori et al 2011) or DRB1*01 (Romero-Pinel et al 2011) is also present in the genotype. These two studies only reported HLA typing to the 2 digit level, but given that DRB1*04 contains a mixture of alleles that do or do not encode proteins with an E at β71/β74 of the HLA-DR molecule, as discussed above, and that the presence or absence of an E at β71/β74 appears to skew the likelihood that the genotype will contain DRB1*15:01, it could be speculated that the correlation with disease severity might only occur in those DRB1*04 molecules with an E at β71/β74.…”
Section: Effects Of Hla On the Severity Of Msmentioning
confidence: 96%
“…The presence of HLA-B*44 (Healy et al 2010), DRB1*14 (in DRB1*15:01 negative genotypes) (Liguori et al 2011) or DRB1*10 (in DRB1*15:01 positive genotypes) (Liguori et al 2011) has been reported to preserve brain parenchymal volume and reduce the burden of T2 hyperintense lesions. Using an extremes of outcome design, in which only patients from the extremes of distribution of long-term outcome are considered, DRB1*01 was found to be underrepresented in malignant vs benign cases of MS (DeLuca et al 2007).…”
Section: Effects Of Hla On the Severity Of Msmentioning
confidence: 97%